A New Thinking: Deciphering the Aberrance and Clinical Implication of IGF Axis Regulation Pattern in Clear Cell Renal Cell Carcinoma - Jiang, Aimin; Wu, Xiaofeng; Wang, Desheng; Wang, Anbang; Dong, Kai; Liu, Bing; Qu, Le; Luo, Peng; Wang, Jian; Tong, Qiang; Wang, Linhui (Frontiers in Immunology, 2022)
Rationale: The recent research found that IGF regulator genes played a pivotal role in multiple biological process, which may be developed for cancer treatment. However, the characteristics and implication of IGF regulators in cancers, especially in clear cell renal cell cancer (ccRCC), remain elusive. Methods: We systematically analyzed the expression, prognostic valuation, genome variation, functional implication at pan-cancer level from The Cancer Genome Atlas. According to expression level of IGF regulator genes, ccRCC could be divided into three different subtypes via unsupervised cluster algorithm: IGF-pattern cancer type1 (IPCS1), type2 (IPCS2) and type3 (IPCS3). The immune microenvironment, immunotherapy response, metabolic pattern, tumor progression signature among the three subgroups were investigated. The clinical characteristics, genomic mutations and potential drug sensitivity were further analyzed. IGF-pattern related risk model was constructed to predict RCC patients’ outcome. Finally, SHC1, a potential IGF axis target, was comprehensively investigated in ccRCC. Results: We found that IGF regulator genes were specifically up-regulated in various cancer tissues, which were correlated with copy number variations and dysregulated pathways. IPCS1, IPCS2 and IPCS3 exhibited different clinical profiles and biological characteristics in ccRCC. IPCS3 subtype indicated a higher clinical stage and a worse survival, IPSC3 ccRCC displayed activated metabolic signatures to fuel the cancer progression. IPCS3 subgroup hold a higher tumor mutation burden and lower immune activities, which resulted a low ICI therapy response and tumor immunity dysfunction state. The genome-copy numbers of IPCS2/3, including arm-gain and arm-loss was significantly higher than IPCS1. Besides, the drug sensitivity profiles was different among the three subgroups. The prognostic risk model based on subtype’s biomarker exerted a promising performance both in training and validation cohorts. Finally, up-regulated expression of SHC1 partly induced poorer immunotherapy response and shorter survival of ccRCC patients. Conclusion: Targeting IGF regulators may be functioned as a treatment approach among multi cancers. IGF regulator-related signature could reshape the tumor immune microenvironment via activating multi-step immune programs. The inhibition of SHC1 may enhance the efficacy of immunotherapy, and SHC1 could be a suitable target for ccRCC therapy.